SIRT5 Deficiency Enhances Susceptibility to Kainate-Induced Seizures and Exacerbates Hippocampal Neurodegeneration not through Mitochondrial Antioxidant Enzyme SOD2 - Li, Fengling; Liu, Lei (Frontiers in Cellular Neuroscience, 2016)
Epilepsy is a common and serious neurological disorder characterized by occurrence of recurrent spontaneous seizures, and emerging evidences support the association of mitochondrial dysfunction with epilepsy. Sirtuin 5, localized in mitochondrial matrix, has been considered as an important functional modulator of mitochondria that contributes to ageing and neurological diseases. Our data shows that SIRT5 deficiency strikingly increased mortality rate and severity of response to epileptic seizures, dramatically exacerbated hippocampal neuronal loss and degeneration in mice exposed to kainate, and triggered more severe reactive astrogliosis. We found that the expression of mitochondrial SIRT5 of injured hippocampus was relatively up-regulated, indicating its potential contribution to the comparably increased survival of these cells and its possible neuroprotective role. Unexpectedly, SIRT5 seems not to apparently alter the decline of antioxidant enzymes superoxide dismutase 2 and glutathione peroxidase in hippocampus caused by kainate exposure in our paradigm, which indicates that the protective roles of SIRT5 on seizures and cellular degeneration might through different regulatory mechanisms that would be explored in the future. In the present study, we provided strong evidences for the first time to demonstrate the association between SIRT5 and epilepsy, which offeres a new understanding of the roles of SIRT5 in mitochondrial functional regulation. The neuroprotection of SIRT5 in kainate-induced epileptic seizure and neurodegeneration will improve our current knowledge of the nature of SIRT5 in central nervous system and neurological diseases.